2000
DOI: 10.1080/14759390000200096
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting teachers' use of information and communications technology: a review of the literature

Abstract: This article reports on the literature associated with practising teachers' uptake of information and communications technology (ICT). Studies reveal a number of factors which influence teachers' decisions to use ICT in the classroom: access to resources, quality of software and hardware, ease of use, incentives to change, support and collegiality in their school, school and national polices, commitment to professional learning and background in formal computer training. The review highlights the role of pedag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
303
2
44

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 664 publications
(409 citation statements)
references
References 27 publications
16
303
2
44
Order By: Relevance
“…Pour ce qui est des défis, la CA n'aura pas permis à certaines enseignantes de se sentir mieux outillées dans le domaine de l'intégration technologique (Bruce, Campbell, Wang, Hsu, Duffy et Wolf, 2010), et en particulier concernant l'utilisation du TBI. Ce défi fait écho aux recherches, dont celles de Lussier et al (2007), Mumtaz (2000), Zhao et Cziko (2001), qui précisent que les enseignants n'ont pas confiance en leurs compétences en matière d'intégration des technologies. De plus, ces recherches tendent à démontrer que les enseignants manquent d'occasions de développement professionnel dans ce domaine (Ping Lim et Sing Chai, 2008); le contexte de l'enseignement des S-T y serait pourtant facilitant.…”
Section: Une Ca Qui Satisfait Aux Besoins Cognitifs Affectifs Et Idéunclassified
“…Pour ce qui est des défis, la CA n'aura pas permis à certaines enseignantes de se sentir mieux outillées dans le domaine de l'intégration technologique (Bruce, Campbell, Wang, Hsu, Duffy et Wolf, 2010), et en particulier concernant l'utilisation du TBI. Ce défi fait écho aux recherches, dont celles de Lussier et al (2007), Mumtaz (2000), Zhao et Cziko (2001), qui précisent que les enseignants n'ont pas confiance en leurs compétences en matière d'intégration des technologies. De plus, ces recherches tendent à démontrer que les enseignants manquent d'occasions de développement professionnel dans ce domaine (Ping Lim et Sing Chai, 2008); le contexte de l'enseignement des S-T y serait pourtant facilitant.…”
Section: Une Ca Qui Satisfait Aux Besoins Cognitifs Affectifs Et Idéunclassified
“…It is generally acknowledged in the literature that getting ICT professional development 'right' is very difficult to achieve (Mumtaz 2000, Selwood et al 2000, Visscher & Brandhorst 2001, McDougall & Squires 1997. At the same time, despite the difficulties, there is also recognition that there are critical links between staff ICT ability and staff ICT use, and staff ICT ability and student ICT ability (Kennewell et al 2000, Russell et al 2000).…”
Section: Ict Abilitymentioning
confidence: 99%
“…Case studies reflecting successful computer integration have all shown such schools to be provided with excellent facilities, technical backup and financial resources (Mumtaz 2000). Other writers express reservations that access to ICT, on its own, will provide positive educational outcomes (Cuban 2000).…”
Section: Ict Accessmentioning
confidence: 99%
See 2 more Smart Citations